2019
DOI: 10.1016/j.jad.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic polypharmacy reconsidered: Between-class polypharmacy in the context of multimorbidity in the treatment of depressive disorders

Abstract: Objectives: Both psychiatric polypharmacy and multimorbidity are common in depressed adults. We examine recent patterns of psychotropic polypharmacy with attention to concurrent multimorbidity in the treatment of depressive disorders in outpatient psychiatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
0
15
2
Order By: Relevance
“…The present study discerned most inpatients with depressive disorders to receive multiple psychotropic and non-psychotropic drugs. Rhee and Rosenheck found that 58% of depressed adults in their sample from office-based psychiatric care received more than one psychotropic drug simultaneously [79]. This number was slightly lower than the number in the present total sample (65%, not shown in Figures).…”
Section: The Present Study In Comparison To Previous Researchcontrasting
confidence: 70%
“…The present study discerned most inpatients with depressive disorders to receive multiple psychotropic and non-psychotropic drugs. Rhee and Rosenheck found that 58% of depressed adults in their sample from office-based psychiatric care received more than one psychotropic drug simultaneously [79]. This number was slightly lower than the number in the present total sample (65%, not shown in Figures).…”
Section: The Present Study In Comparison To Previous Researchcontrasting
confidence: 70%
“…disorders to receive multiple psychotropic and nonpsychotropic drugs. Rhee and Rosenheck found that 58% of depressed adults in their sample from office-based psychiatric care received more than one psychotropic drug simultaneously [79]. This number was slightly lower than the number in the present total sample (65%, not shown in Figures).…”
Section: The Present Study In Comparison To Previous Researchcontrasting
confidence: 70%
“…Despite common prescription of multiple psychotropic medications in various populations (e.g., psychiatric, elderly, dementia, and community-dwelling population) (Hartikainen et al, 2005;Brett et al, 2017;Nørgaaard et al, 2017;Rhee and Rosenheck, 2019), very few studies focused on the effects of psychotropic polypharmacy. Nevertheless, an association between the use of multiple psychotropic drugs and falls in older adults has been reported.…”
Section: Discussionmentioning
confidence: 99%